Lysine-targeting inhibition of amyloid β oligomerization by a green perilla-derived metastable chalcone in vitro and in vivo. Issue 12 (27th October 2022) - Murakami, Kazuma; Sakaguchi, Yoshiki; Taniwa, Kota; Izuo, Naotaka; Hanaki, Mizuho; Kawase, Taiji; Hirose, Kenji; Shimizu, Takahiko; Irie, Kazuhiro
Abstract : We propose a site-specific inhibition of Aβ42 oligomerization by the green perilla-derived chalcone DDC, which is converted to its decomposed flavonoids (1–3 ) via nucleophilic aromatic substitution with water molecules, in vitro and in vivo . Abstract : Oligomers of amyloid β (Aβ) represent an early aggregative form that causes neurotoxicity in the pathogenesis of Alzheimer's disease (AD). Thus, preventing Aβ aggregation is important for preventing AD. Despite intensive studies on dietary compounds with anti-aggregation properties, some identified compounds are susceptible to autoxidation and/or hydration upon incubation in water, leaving unanswered issues regarding which active structures in metastable compounds are actually responsible for the inhibition of Aβ aggregation. In this study, we observed the site-specific inhibition of 42-mer Aβ (Aβ42) oligomerization by the green perilla-derived chalcone 2′, 3′-dihydroxy-4′, 6′-dimethoxychalcone (DDC), which was converted to its decomposed flavonoids (dDDC, 1–3 ) via nucleophilic aromatic substitution with water molecules. DDC suppressed Aβ42 fibrillization and slowed the transformation of the β-sheet structure, which is rich in Aβ42 aggregates. To validate the contribution of dDDC to the inhibitory effects of DDC on Aβ42 aggregation, we synthesized 1–3 and identified 3, a catechol-type flavonoid, as one of the active forms of DDC. 1 H– 15 N SOFAST-HMQC NMR revealed that 1–3 as well as DDC could interact with residues between His13 and Leu17, which were near the intermolecular β-sheet (Gln15–Ala21). The nucleation in Aβ42 aggregates involves the rate-limiting formation of low-molecular-weight oligomers. The formation of a Schiff base with dDDC at Lys16 and Lys28 in the dimer through autoxidation of dDDC was associated with the suppression of Aβ42 nucleation. Of note, in two AD mouse models using immunoaffinity purification-mass spectrometry, adduct formation between dDDC and brain Aβ was observed in a similar manner as reported in vitro . The present findings unraveled the lysine-targeting inhibitory mechanism of metastable dietary ingredients regarding Aβ oligomerization.